2000
DOI: 10.1007/s007750000147
|View full text |Cite
|
Sign up to set email alerts
|

On the role of strain in blue copper proteins

Abstract: Theoretical investigations of the structure and function of the blue copper proteins are described. We have studied the optimum vacuum geometry of oxidised and reduced copper sites, the relative stability of trigonal and tetragonal Cu(II) structures, the relation between the structure and electronic spectra, the reorganisation energy, and reduction potentials. Our calculations give no support to the suggestion that strain plays a significant role in the function of these proteins; on the contrary, our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
114
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 31 publications
21
114
1
Order By: Relevance
“…There have been numerous reports and reviews supporting the entatic/rack-induced state hypothesis (7,13,19,20,26,59). On the other hand, theoretical and experimental studies have questioned the role of the protein matrix in defining the geometry of the copper center (21,22,24,25). X-ray studies on the apo form of several cupredoxins, showing no changes in the ligands' conformations upon removal of the copper ion, were considered as experimental evidence of the entatic/rack-induced hypothesis for ET copper proteins (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous reports and reviews supporting the entatic/rack-induced state hypothesis (7,13,19,20,26,59). On the other hand, theoretical and experimental studies have questioned the role of the protein matrix in defining the geometry of the copper center (21,22,24,25). X-ray studies on the apo form of several cupredoxins, showing no changes in the ligands' conformations upon removal of the copper ion, were considered as experimental evidence of the entatic/rack-induced hypothesis for ET copper proteins (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…This scenario, known as the entatic/rack-induced state hypothesis, was originally formulated for protein-bound cofactors by Lumry and Eyring in 1954 (16) and then extended to electron transfer metalloproteins by Malmström and Williams in the late 1960s (17,18). This concept has been matter of debate along many years (7,15,(19)(20)(21)(22)(23)(24)(25)(26). In particular, Ryde et al have reported in vacuum quantum calculations suggesting the absence of any strain in the geometry adopted by the copper in the protein framework (21,22).…”
mentioning
confidence: 99%
“…In addition, there are two weaker ligands from a backbone carbonyl group (covalently connected to one of the His ligands and therefore modelled by CH 3 CONHCH 2 CH 2 -imidazole) and the side chain of a Met residue (modelled by CH 3 SCH 3 ), forming a trigonal bipyramidal geometry. The bond distances to the latter two ligands are strongly affected by the surrounding protein [38], so we constrained them to the distance found in crystal structures [72,73]. We have studied this site in both the reduced Cu + (closed-shell singlets) and the oxidised Cu 2+ states (doublet), and we have measured the strength of hydrogen bonds between a probe water molecule and each of the five ligands, i.e.…”
Section: Azurin Modelsmentioning
confidence: 99%
“…We study how the hydrogen-bond strength depends on the type of metal and its oxidation state, the coordination number, the type of the ligand, other ligands of the metal, and on the nature of the second-sphere hydrogen-bond partner. We study over 60 different complexes, taken mainly from our previous theoretical studies of various metalloproteins [18,19,22,38,39,40,41,42,43,44,45,46,47]. The results provide much insight into how metal coordination affects the geometry and energy of hydrogen bonds to ligating…”
Section: Introductionmentioning
confidence: 99%
“…These structures have formed the basis for a detailed understanding of the biological function of the proteins by elucidating the interplay between the electronic and geometric structure of the metal site (8,15,(32)(33)(34). However, the geometric structures were all determined in the solid state.…”
mentioning
confidence: 99%